Semic verbalisation: A systematic procedure for the replication of meaning in translating lexical items - Martín García, Adolfo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The purpose of this article is to introduce a systematic translation procedure called Semic Verbalisation (SV), which draws on componential analysis so as to first lexicalise and then translate a word's sense components. While construing a hybrid denotational-mentalistic conception of meaning, a series of steps will be formulated that are useful for solving various prac-tical translation problems. The procedure is based on philosophy of lan-guage (Russell, Tarski, Frege, Quine and Wittgenstein), linguistics (Katz & Fodor) and translation studies (in particular Newmark). Its practical appli-cations for translation studies will be illustrated, and, in the discussion, its advanta ges and drawbacks will be scrutinised from both a theoretical and a practical perspective